2019
DOI: 10.1097/01.ju.0000556646.77448.3d
|View full text |Cite
|
Sign up to set email alerts
|

Mp56-09 effect of Filling Rate on Bladder Sensation Event Descriptors in Overactive Versus Healthy Bladders During Non-Invasive Hydration Studies

Abstract: between the groups. The percentage varied significantly between NF (27.6AE11%) compared to IAEMG (40.6AE31%) p<0.0001.CONCLUSIONS: We have shown that a system of normalizing, smoothing and standardizing flows has a significant impact on the Qmax, and Qmax flow index aside from the timed based measures that were routinely prone to errors in doing the calculations necessary to obtain uroflow results. These time-based errors further erode the quality and confidence of any data we obtain that is determined by urof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(30 reference statements)
1
3
0
Order By: Relevance
“…Our dynamic analysis was performed separately for each individual and is free of these limitations. Another study in concert with our observations reports on the bladder sensations in normal (n = 12) and OAB (n = 17) participants during the oral hydration by rapid consumption of 2L of Gatorade [37]. One conclusion was "this study showed fast filling can lead normal individuals to experience OAB sensations because sensation event patterns in normal participants during fast filling were similar to OAB participants during slow filling."…”
Section: Plos Onesupporting
confidence: 71%
See 1 more Smart Citation
“…Our dynamic analysis was performed separately for each individual and is free of these limitations. Another study in concert with our observations reports on the bladder sensations in normal (n = 12) and OAB (n = 17) participants during the oral hydration by rapid consumption of 2L of Gatorade [37]. One conclusion was "this study showed fast filling can lead normal individuals to experience OAB sensations because sensation event patterns in normal participants during fast filling were similar to OAB participants during slow filling."…”
Section: Plos Onesupporting
confidence: 71%
“…While "fast filling" BFR is similar to observed during the peaks of BFR in our BDs, the "slow filling" BFR was about 6-fold higher than mean BFR (*1 mL/min) across the 3-day BDs in our study. It would be of interest to see the results of oral hydration study with slower "slow filling"; in this case, differences in bladder sensations during "slow" and "fast" filling might be even higher than observed in [37].…”
Section: Plos Onementioning
confidence: 99%
“…23 Sensation events and descriptors have been compared between OAB and CONs without the corresponding fMRI data. 24 Adopting the bladder sensation meter to MRI use will further advance our understanding of urgency during bladder filling and OAB phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Some patients with overactive bladder who did not “respond” to bladder filling (ie, OAB-1 group) and controls may not have done so because their bladder was not full enough to trigger the urgency sensation. Prior naturalistic bladder-filling studies have used higher fluid intake volumes, such as 2000 mL G2-Gatorade (for participants to drink as fast as feasible) 2,3 or 600 mL water (for participants to drink within 5 minutes), 4 compared with the 350 mL we used in our protocol. However, these studies did not include neuroimaging, which presents unique experimental challenges in regard to fluid volume, intake timing, overall patient burden, and head motion (eg, participant may move inside the MRI scanner if the urgency sensation is too intense).…”
mentioning
confidence: 99%